Compliance of Halal-Certified Business Actors with Environmentally Friendly Business Management from the Perspective of Islamic Business Ethics - Jumailah Jumailah; Khafid Abadi; Tarmidzi; Elsayed Mohamed Salem Elawadi (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2026)
This study is motivated by a paradox in the micro and small-scale food industry, where halal certification is often not directly proportional to environmental management responsibility. Halal labeling should cover all aspects of halalan thayyiban, but in practice, production waste is often neglected and pollutes the ecosystem. This study aims to analyze the level of compliance of halal-certified businesses with environmental management standards and to examine this phenomenon through the perspective of Islamic business ethics, particularly the principles of khalifah (stewardship of the earth) and hifz al-bi'ah (preservation of the environment). The research method used was descriptive qualitative with a sociological-legal approach. Data was collected through in-depth interviews with MSME actors, field observations of waste disposal systems, and documentation of relevant regulations. The research location focused on food businesses in the Pekalongan area that already had halal certificates, either through the regular scheme or self-declaration. The results of the study show that business actors' compliance with environmental management is still administrative in nature and has not yet become a substantial ethical awareness. Most business actors view halal certification as limited to the ritual cleanliness of raw materials, while the ecological impact of post-production is considered a separate entity. From the perspective of Islamic business ethics, this practice shows that the value of thayyib has not been fully internalized. This study recommends the integration of halal product assurance instruments with environmental management standards in order to create a sustainable halal industry ecosystem that is beneficial to nature.